Real-Time GNSS satellite SISRE and its integrity for LEO satellite POD - Chen, Beixi; Wang, Kan; El-Mowafy, Ahmed; Yang, Xuhai (2024)
The real-time Global Navigation Satellite System (GNSS) precise orbital and clock products are essential prerequisites for the Positioning, Navigation, and Timing (PNT) services and have been assessed in various studies. Compared to the precision of the orbital and clock products, their combined effect expressed in Signal-In-Space Ranging Error (SISRE) is of higher concern for positioning users. As a special user of the GNSS, the Low Earth Orbit (LEO) satellites need high-precision real-time GNSS products for their Precise Orbit Determination (POD) and clock determination in real time, which enables the future LEO-augmented GNSS PNT service. This study performs a comprehensive analysis of the real-time GNSS products from five different analysis centers, including analysis of their continuity, accuracy of their orbits, precision of their clocks, and their SISREs for LEO satellites at different altitudes. Using the tested products, the LEO POD was also performed to verify the correlation between the quality of the GNSS products and the accuracy of the LEO POD. Furthermore, to assess the integrity of real-time GNSS products, the overbounding standard deviations and mean values of the combined clock and orbital errors were computed and compared for different institutions. It was found that the GPS and Galileo SISRE range from a few centimeters to around 8 cm, while the SISRE of the Beidou Satellite Navigation System (BDS) Medium Earth Orbit (MEO) is a bit worse, i.e., around 1-2 dm. It has been demonstrated that there exists a positive correlation between the SISRE and user altitude, which implies a higher bias introduced to LEO satellites than ground users. The overbounding standard deviations and mean values of the GPS and Galileo products are all within 1 dm, whereas for BDS they are about 1-2 dm. Among the tested products, the smallest SISRE and overbounding values were delivered by the National Centre for Space Studies (CNES) in France for GPS and Galileo, while the GNSS Research Center of Wuhan University (WHU) provided the best accuracy and integrity for the BDS MEO products.